2016
DOI: 10.1017/s0031182016001487
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase-3 is involved in glycogen metabolism control and embryogenesis of Rhodnius prolixus

Abstract: Rhodnius prolixus is a blood-feeding insect that transmits Trypanosoma cruzi and Trypanosoma rangeli to vertebrate hosts. Rhodnius prolixus is also a classical model in insect physiology, and the recent availability of R. prolixus genome has opened new avenues on triatomine research. Glycogen synthase kinase 3 (GSK-3) is classically described as a key enzyme involved in glycogen metabolism, also acting as a downstream component of the Wnt pathway during embryogenesis. GSK-3 has been shown to be highly conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Glycogen synthase was phosphorylated by a conserved glycogen synthase kinase 3 (GSK3) in eukaryotes, and GSK3 acted as a downstream component of the Wnt pathway during embryogenesis (Vital et al 2010 ). A study demonstrated that GSK3 was involved in regulation of oogenesis and embryogenesis of Rhodnius prolixus (a blood-feeding insect as a media of Trypanosoma ), and the activity and transcription levels of GSK3 were related to glycogen content (Mury et al 2016 ). In Schistosoma japonicum , GSK3β (one GSK3 isoform) was highly expressed in the eggs (Liu et al 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen synthase was phosphorylated by a conserved glycogen synthase kinase 3 (GSK3) in eukaryotes, and GSK3 acted as a downstream component of the Wnt pathway during embryogenesis (Vital et al 2010 ). A study demonstrated that GSK3 was involved in regulation of oogenesis and embryogenesis of Rhodnius prolixus (a blood-feeding insect as a media of Trypanosoma ), and the activity and transcription levels of GSK3 were related to glycogen content (Mury et al 2016 ). In Schistosoma japonicum , GSK3β (one GSK3 isoform) was highly expressed in the eggs (Liu et al 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, adaptive mutations in the Pgm1 locus show latitudinal clinal variation correlating with increased glycogen storage in temperate regions [ 67 , 68 ]. Glycogen storage increases after blood meal in R. prolixus , is required for oogenesis and is completely depleted after prolonged starvation periods [ 69 – 72 ] (Fig. 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although GSKβ3 is a substrate for Akt and therefore has its activity modulated by this kinase, it has been shown that PKA (protein kinase A) and other kinases in the Wnt pathway can also phosphorylate and inactivate this enzyme (91, 92). GSKβ3 was proven to be essential for glycogen metabolism but not lipogenesis during oogenesis and embryogenesis in R. prolixus , in response to both insulin and Wnt receptors (93). Also, triatomine insects, such as R. prolixus , mainly rely on lipids as their motor energy supply, having a remarkably low concentration of sugars in the hemolymph when compared to other insects (94).…”
Section: Discussionmentioning
confidence: 99%